Seabirds and plastics don't mix: Examining the differences in marine plastic ingestion in wedge-tailed shearwater chicks at near-shore and offshore locations. (October 2018) - Verlis, Krista M.; Campbell, Marnie L.; Wilson, Scott P.
Abstract: Plastic ingestion by wedge-tailed shearwaters (WTS) nesting at near-shore and offshore sites along the east coast of Australia were investigated. Ingestion rates were at 20% in near-shore lavaged WTS, where the beaches were significantly more polluted, compared to 8% in birds at offshore sites. The material and colour of recovered plastics at offshore sites differed significantly between beach surveys and that ingested by seabirds in the same area. This pattern was not evident near-shore. Hence, in near-shore environments birds may feed locally and are influenced by nearby plastics, compared to birds offshore. The origins of marine debris between near-shore and offshore beaches differed; with land-based sources unsurprisingly having more influence on near-shore sites. The findings of this study indicate the need for localised data to address and manage this pollutant, with nesting seabirds at greater risk in near-shore environments. A preliminary modified ecological quality objective for WTS is presented. Highlights: Wedge-tailed shearwater chicks had higher plastic Ingestion nearshore than offshore. Nearshore beaches were significantly more polluted than offshore sites. Nearshore plastic traits were similar in beach surveys and that ingested by chicks. Nesting seabirds appear at greater risk in nearshore environments.